Interdisciplinary doctoral research networks: enhancers and inhibitors of social capital development. Issue 12 (1st December 2020) - Mountford, Nicola; Coleman, Matthew; Kessie, Threase; Cusack, Tara
ABSTRACT: Interdisciplinary research networks are increasing, with professionals encouraged to undertake research across disciplines to increase innovation, creativity and knowledge. More recently, this interdisciplinary focus is being mirrored by the establishment of interdisciplinary doctoral research networks. But do these networks work? And if so, how and why? We employ social capital theory to (a) understand the lived experiences of students in interdisciplinary doctoral programmes and (b) build programme design theory to support the development of social capital within such programmes. We present the results of 28 semi-structured interviews conducted with doctoral students from three European Union funded interdisciplinary research training networks to understand how they perceive the enhancers, inhibitors and manifestations of social capital within their networks. Key themes revolve around 'extracting value from the interdisciplinary process', 'motivating students throughout the interdisciplinary programme journey', and 'relating to others both within and external to the programme'. We propose a framework for interdisciplinary programme design.